A new approach to detect non-pleiotropic QTL for correlated traits - A. Carta; J.M. Elsen; S. Casu (Italian Journal of Animal Science, 2010)
In quantitative traits loci (QTL) mapping experiments a number of traits are often recorded. Although most QTL-detection methods are based on single trait analysis, several approaches for multi-trait detection have been proposed (Weller et al., 1996; Knott and Haley, 2000). Those methods mainly focus on either increasing power of detecting pleiotropic QTL or discriminating between pleiotropy and linkage, often with the aim of dissecting unfavourable genetic correlation between traits. Nevertheless, when two traits are positively correlated, the detection of genes only affecting one of them could allow the speeding of its genetic improvement.